2021
DOI: 10.1111/jpr.12321
|View full text |Cite
|
Sign up to set email alerts
|

The Vietnamese Version of the Gratitude Questionnaire (GQ) and the Revised Short Gratitude, Resentment, and Appreciation Test (S‐GRAT): Psychometric Properties Among Adolescents

Abstract: There is a lack of validated instruments to measure gratitude in Vietnamese adolescents; this issue is regarded as a significant impediment to progress in implementing empirical research on the gratitude of Vietnamese adolescents. The aim of this study, therefore, was to validate the Vietnamese translation of the Gratitude Questionnaire (GQ) and the Revised Short Gratitude, Resentment, and Appreciation Test (S-GRAT), using two independent samples of Vietnamese adolescents in two studies. In Study 1, Sample 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…With respect to convergent validity, the results showed that the total score of the S-GRAT-Gr and the scores of its subscales were moderately to strongly positively correlated with the GQ-6 score. The results are consistent with previous research findings in adult samples (Froh et al, 2011;Jans-Beken et al, 2015;Tran et al, 2022) and indicate that both scales assess the conceptualization of grateful disposition. Moreover, nomological network analysis showed that both the total score of the S-GRAT-Gr and the score of the subscales presented positive correlations with life satisfaction and happiness.…”
Section: Convergent Validity Of S-grat-grsupporting
confidence: 92%
See 3 more Smart Citations
“…With respect to convergent validity, the results showed that the total score of the S-GRAT-Gr and the scores of its subscales were moderately to strongly positively correlated with the GQ-6 score. The results are consistent with previous research findings in adult samples (Froh et al, 2011;Jans-Beken et al, 2015;Tran et al, 2022) and indicate that both scales assess the conceptualization of grateful disposition. Moreover, nomological network analysis showed that both the total score of the S-GRAT-Gr and the score of the subscales presented positive correlations with life satisfaction and happiness.…”
Section: Convergent Validity Of S-grat-grsupporting
confidence: 92%
“…These findings seem to suggest that gratitude is a universal feeling, in which noticing and receiving something valuable causes feelings of appreciation for the positive in the world. Furthermore, these findings also suggest that the benefits of gratitude may have an impact both on Western individualistic societies but also on Eastern collectivistic societies (Tran et al, 2022).…”
Section: The Present Studymentioning
confidence: 73%
See 2 more Smart Citations
“…In nonwestern settings, scholars like Naito and Sakata (2010), Chan (2010), andGarg et al (2021) have relied on GRAT-16 to explore interrelationships between gratitude and other variables like happiness, vitality, and satisfaction with life. These studies were conducted in India (Garg, 2020;Mahipalan & Sheena, 2019), China (Kong et al, 2014), Japan (Naito & Sakata, 2010), and Vietnam (Tran et al, 2021). Similarly, western authors like Froh et al (2011), Jans-Beken et al (2015, Duran (2017), Hammer and Brenner (2017) have also used GRAT-16 for their empirical studies.…”
Section: Gratitude Resentment and Appreciation Scale (Grat-16)mentioning
confidence: 99%